1995
DOI: 10.1042/bj3060679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on cytoplasmic free Ca2+ concentration in pancreatic β-cells are mediated by interaction with ATP-sensitive K+ channels and L-type voltage-gated Ca2+ channels but not the ryanodine receptor

Abstract: In the pancreatic beta-cell, an increase in the cytoplasmic free Ca2+ concentration ([Ca2+]i) by caffeine is believed to indicate mobilization of Ca2+ from intracellular stores, through activation of a ryanodine receptor-like channel. It is not known whether other mechanisms, as well, underlie caffeine-induced changes in [Ca2+]i. We studied the effects of caffeine on [Ca2+]i by using dual-wavelength excitation microfluorimetry in fura-2-loaded beta-cells. In the presence of a non-stimulatory concentration of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 46 publications
(48 reference statements)
5
51
1
Order By: Relevance
“…In fact, post-OGTT insulin levels were not different in subjects taking active treatment and in those taking placebo, and the curves of such categories of subjects were comparable even for the highest levels of circulating caffeine (Figure 2). This is partially in disagreement with the data of Lambert (Lambert et al, 1967) and of Islam (Islam et al, 1995), who found a caffeine-induced stimulation of insulin release from cultured pancreatic b-cells, and with those of Turtle, who demonstrated an increased insulin secretion with another xanthine (theophylline) (Turtle et al, 1967) and suggested that the in vivo insulin response to caffeine may be completely different from that detected in vitro.…”
Section: Discussioncontrasting
confidence: 55%
“…In fact, post-OGTT insulin levels were not different in subjects taking active treatment and in those taking placebo, and the curves of such categories of subjects were comparable even for the highest levels of circulating caffeine (Figure 2). This is partially in disagreement with the data of Lambert (Lambert et al, 1967) and of Islam (Islam et al, 1995), who found a caffeine-induced stimulation of insulin release from cultured pancreatic b-cells, and with those of Turtle, who demonstrated an increased insulin secretion with another xanthine (theophylline) (Turtle et al, 1967) and suggested that the in vivo insulin response to caffeine may be completely different from that detected in vitro.…”
Section: Discussioncontrasting
confidence: 55%
“…Another key property of RyRs is that caffeine at millimolar concentrations can pharmacologically cause channel opening. In some studies, caffeine did not activate Ca 2+ release from the internal stores of β-cells [14,15], whereas Ca 2+ release from the internal stores was activated if caffeine-sensitive RyRs were present in intact β-cells [16,17]. In fact, the presence of RyRs in insulin secreting β-cells is well-accepted at the present time, although the expression of each type of RyRs is variable, depending on the species studied.…”
Section: Elevation Of the Intracellular Free Calcium Concentration ([Camentioning
confidence: 70%
“…Besides mobilization of intracel-lular Ca 2+ pools, a variety of other effects have been discovered with caffeine, e.g., activation (Steenbergen & Fay, 1996) or inhibition of Ca 2+ sequestration (Chapman & Tunstall, 1988;Bassani, Bassani & Beers, 1994) or Ca 2+ release (Missiaen, Taylor & Berridge, 1992) as well as some other unrelated effects (Gupta et al, 1990;Berridge, 1991;Sawynok & Yaksh, 1993;Tanaka & Tashjian, 1993;Combettes, Berthon & Claret, 1994;Islam et al, 1995). Despite these uncertainties caffeine has remained a popular tool in secretion studies, partly because it is easy to apply and partly because of the lack of physiological alternatives.…”
Section: Introductionmentioning
confidence: 99%